Can the running-based anaerobic sprint test be used to predict anaerobic capacity? - Kaminagakura, Edson I.; Zagatto, Alessandro M.; Redkva, Paulo E.; Gomes, Elton B.; Loures, João P.; Kalva-Filho, Carlos A.; Papoti, Marcelo [UNESP] (My University, 2012)
The purpose of this study was to determine if the use of the running-based anaerobic sprint test (RAST) could be used to predict anaerobic capacity in running athletes. Eleven male middle-distance runners (21 ± 1 yrs) volunteered to take part in this study. The maximum accumulated oxygen deficit (MAOD) was determined during running on a treadmill, and the RAST was determined during running on a track. None of the variables associated with RAST output (peak power, mean power, fatigue index, and maximal and mean velocities) was significantly correlated with MAOD. Thus, the findings indicate that the use of the RAST does not predict anaerobic capacity in running. © 1997-2012 American Society of Exercise Physiologists.
Keywords: Anaerobic capacity; MAOD; RAST; Running